(untitled) (Indian Journal of Public Health Research & Development, 2020)
Sleep is equally important to the food we eat, the liquids we drink, or the safety of the children. Each living being needs sleep. It is the essential activity of the mind during each stage of development. Whereas inadequate sleep can lead to the development of various health issues. Although a generous group of literature has explored the relationship between sleep patterns and problems, comprehensive reviews and far-reaching conclusions are lacking. This systematic review was conducted to describe the sleep pattern or habits present in Children and also to identify its influence on the onset of various sleep problems among 3 to 18 years. Electronic databases were searched for articles published up to August 2019 and no limits for study designs were kept. The articles for review were obtained from databases like MEDLINE, PubMed, Cochrane, and Google Scholar along with a handful of references of experts using Boolean operators’ search criteria. The guidelines adopted were Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The nighttime sleep duration was the most common sleep measure or variable in 73% of the articles. The average sleep duration (night time) is 9.811 hours (3 to 5 years), 9.082 hours (6 to12 years) and 7.944 hours (12 to 18 years). The result from this review suggested that sleep patterns tend to delay as the age increases leading to insufficient sleep and irregular bedtime schedules leading to the onset of some of the sleep problems like snoring, nightmare, bedwetting, etc. A few reviews suggested that it was difficult to define the sleep problem effectively as families vary greatly in their tolerance of their children’s sleeping habits.